2021
DOI: 10.3762/bjnano.12.82
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the structural, optoelectronic and thermophysical properties of the π-SnSe for thermoelectric applications

Abstract: Tin selenide (SnSe) has thermoelectric (TE) and photovoltaic (PV) applications due to its exceptional advantages, such as the remarkable figure of merit (ZT ≈ 2.6 at 923 K) and excellent optoelectronic properties. In addition, SnSe is nontoxic, inexpensive, and relatively abundant. These aspects make SnSe of great practical importance for the next generation of thermoelectric devices. Here, we report structural, optoelectronic, thermodynamic, and thermoelectric properties of the recently experimentally identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 79 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…The effects of defect engineering and strain engineering on the performance of SnSe are also worthy of in‐depth study. Finally, the simulation results showed that the π‐SnSe also has prospective applications in optoelectronics, [ 95,225 ] which requires further exploration.…”
Section: Applicationsmentioning
confidence: 99%
“…The effects of defect engineering and strain engineering on the performance of SnSe are also worthy of in‐depth study. Finally, the simulation results showed that the π‐SnSe also has prospective applications in optoelectronics, [ 95,225 ] which requires further exploration.…”
Section: Applicationsmentioning
confidence: 99%